Penilaian Program Praktikum: Model Pembentukan dan Peningkatan Kualiti Guru Praperkhidmatan di Institut Pendidikan Guru Malaysia - Azizah, Sarkowi (2012)
This study aims to evaluate the practicum program based on preservice teachers‟ quality formation and growth model at Malaysian Institute of Teacher Education (IPGM). Multi-point prospective panel research design was conducted on 541 Bachelor in Teaching (PISMP) preservice teachers at five IPGM campuses located in Pulau Pinang, Kedah, and Perlis. Four instruments were adapted from FIT-Choice Scale, Psychological Capital Questionnaire (PCQ), School-Level Environment Questionnaire (SLEQ), and Mentoring for Effective Primary Science Teaching (MEPST). Teacher quality and practicum engagement instruments were developed based on the PISMP objectives. Model of teachers‟ quality formation was analyzed using Structural Equation Modeling (SEM). Results indicated that practicum engagement, positive psychological capital, factors influencing teaching profession, mentor teacher‟s guidance, and school environment explained the 76% variance in teachers‟ quality. Positive psychological capital and practicum engagement had significant direct effects on teacher quality, whereas practicum engagement, positive psychological capital, mentor teacher‟s guidance, and school environment only significantly mediate. Model of teachers‟ quality growth was analyzed using Latent Growth Curve Model based on panel data over three practicum phases. Findings showed that there were significant increases in teacher‟s quality for each phase. In the first phase, SPM grade A was not a significant predictor of teacher‟s quality, but neither grade nor gender significantly predicted the increasing rate of teacher‟s quality. Emphasis should be given to the development of psychological capital and improvement of the practicum activities without neglecting the role of school‟s psychosocial environment and mentor teacher‟s guidance as a catalyst. This study supports the initiatives to strengthen the practicum training, which is part of the 10th Malaysian Plan. Therefore, these models can be applied in future program evaluations at IPGMs in the quest for enhancing teacher training.